PENGARUH MODEL PEMBELAJARAN STUDENT CENTRED LEARNING (SCL) DAN TEACHER CENTRED LEARNING (TCL) TERHADAP MOTIVASI BELAJAR SISWA MTs DITINJAU DARI JENIS KELAMIN - Endang Indayani; Nefi Darmayanti; Khairina Siregar (JIVA: Journal of Behaviour and Mental Health, 2023)
ABSTRACTThe purpose of this research was to determine the effect of student centered learning (SCL) and teacher centered learning (TCL) models on the learning motivation of MTs students in terms of jenis kelamin. The sample is 80 students of superior class. Collection method with Purposive Sampling technique. The researcher designed a self-designed learning motivation variable questionnaire based on the theoretical aspects of Chernis & Goleman (2001) there were 8 behavioral indicators with 44 items. There are 30 valid and valid items. TCL in the form of a conventional learning model. SCL with STAD type learning model. Data analysis using 2-way Anava. The results of the study concluded that there was a significant difference between the learning motivation of students taught by the SCL and TCL learning models, with a coefficient of F=16,766 with a value of p = 0.000 or p <0.05. There is no difference in learning motivation between female and male students with a coefficient of F = 2.007 with p = 0.161 or p > 0.05. There is no effect of the interaction of the learning model with the jenis kelamin of students on learning motivation with a coefficient of F=0.363 with p>0.05.Keywords: Student Centred Learning (SCL), Teacher Centred Learning (TCL), Learning Motivation, Jenis kelamin ABSTRAKTujuan penelitian ini dilakukan adalah untuk mengetahui pengaruh model pembelajaran student centred learning (SCL) dan teacher centred learning (TCL) terhadap motivasi belajar siswa MTs ditinjau dari jenis kelamin. Sampel berjumlah 80 siswa kelas unggulan. Metode pengumpulan dengan tekhnik Purpossive Sampling. Kuesioner variabel motivasi belajar peneliti rancang sendiri berdasarkan aspek teori Chernis & Goleman (2001) ada 8 indikator perilaku dengan 44 item. Item yang valid dan sahih ada 30 item. TCL dalam bentuk model pembelajaran konvensional. SCL dengan model pembelajaran tipe STAD. Analisa data menggunakan Anava 2 Jalur. Hasil penelitian menyimpulkan terdapat perbedaan yang signifikan antara motivasi belajar siswa yang diajarkan dengan model pembelajaran SCL dengan TCL, dengan koefisien F=16.766 bernilai p=0.000 atau p<0.05. Tidak terdapat perbedaan motivasi belajar antara siswa yang berjenis kelamin perempuan dengan laki-laki dengan koefisien F=2.007 dengan p = 0.161 atau p > 0.05. Tidak ada pengaruh interaksi model pembelajaran dengan jenis kelamin siswa terhadap motivasi belajar dengan koefisien F = 0.363 dengan p > 0.05.Kata Kunci : Model Pembelajaran Student Centred Learning (SCL), Teacher Centred Learning (TCL), Motivasi Belajar, Jenis Kelamin.